Adjuvant Interventions in Levofloxacin-Exposed Rabbit Achilles Tendons: An Exploratory Controlled Pilot Study with Histopathological and Ultrasonographic Endpoints - Oana-Maria Mișcă; Liviu-Coriolan Mișcă; Andreea-Adriana Neamțu; Laura Maghiar; Cristian Constantin Croicu; Flavia Baderca; Amalia Raluca Ceaușu; Oana Cristina Radulescu; Valentin-Cristian Iovin; Titus Grecu; Roxana-Cristina Grecu; Alexandra-Magdalena Ioana; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Fluoroquinolones cause Achilles tendinopathy within a narrow, early therapeutic window, yet preventive strategies given alongside these antibiotics remain largely untested. This exploratory pilot study assessed whether four mechanistically distinct adjuvants attenuated histopathological tendon change in a rabbit model of levofloxacin exposure. Methods: Twenty-one male New Zealand White rabbits received oral levofloxacin (100 µg/kg/day, seven days). A contralateral-limb design yielded 42 tendons (two cohorts provided paired limb-specific comparisons and a third cohort received the systemic intervention). Animals were allocated to various groups, receiving platelet-rich plasma (PRP), injectable porcine collagen, oral vitamin E + selenium, topical essential oils with augmented soft-tissue mobilization (ASTM), or a levofloxacin-only control. The main outcome was a modified Bonar composite (tenocyte morphology, cellularity, vascularity, paratendinous fibrosis; 0–12) at three months; additional outcomes were the individual domains and ultrasonographic tendon thickness. Results: Composite scores were low throughout (group medians 2.0–4.0) and did not differ between groups (H = 3.663, p = 0.45); no domain differed, and the untreated control did not show the greatest change. Within animals, collagen-treated tendons scored higher than the paired essential-oil tendons (median difference +3.0, nominal p = 0.031, Bonferroni-adjusted p = 0.062). Tendon thickness increased by day 14 only with vitamin E + selenium (+14.1%; p = 0.003, and p = 0.006 adjusted for baseline); this finding arose in a separate cohort with thinner baseline tendons, cannot be confidently attributed to the intervention, and was unrelated to histopathology (ρ = −0.02, p = 0.91). Macroscopic findings differed between groups (nominal p = 0.031) without predicting tissue grade. Conclusions: No statistically detectable difference in the study-specific four-domain composite was identified among the treatment conditions; the study lacked a levofloxacin-free control and could not provide a definitive efficacy assessment. The model produced only mild pathology, limiting its power, and neither imaging nor gross inspection predicted tissue-level change. These preliminary observations are hypothesis-generating and are intended to inform the design of an adequately powered confirmatory study. The findings are inconclusive for efficacy; the design cannot distinguish lack of adjuvant efficacy from failure of the model to induce measurable disease.